PENGARUH PARTISIPASI ANGKATAN KERJA (TPAK) DAN TINGKAT PENGANGGURAN TERBUKA (TPT) TERHADAP PDRB DI PROVINSI ACEH - Munawir Munawir; Saharuddin Saharuddin (JURNAL EKONOMIKA INDONESIA, 2023)
The open unemployment rate (TPT) and the labor force participation rate (TPAK) were compared in Aceh Province for the purpose of this studyaffected the gross regional product (GDP). Secondary data from BPS and Plantation Statistics were used in this study. VAR is the data analysis technique employed in this study. The study's findings indicate that TPAK and TPT have no impact on GRDP and that, according to the GRDP's granger causality technique, there is no reciprocal association between TPAK and TPT (causality).